Answers

2016-07-06T14:35:44+08:00
2016-07-06T15:17:17+08:00
Use the quadratic formula.. x=[ -b plus or minus the square root of (b squared minus 4ac)] divided by 2a

x squared + 5x - 4=0
let:
a=1, b=5, c= -4

x={ -5 +/- the square root of [5 squared minus 4(1)(-4)]} divided by 2(1)
x={ -5 +/- the square root of [25-(-16)]} divided by 2
x={ -5 +/- the square root of 41} divided by 2
x={ -5 +/- 6.40} divided 2

x={-5 + 6.40} divided by 2
x={1.40} divided by 2
x=0.7

x={-5 - 6.40} divided by 2
x={-11.4} divided by 2
x= -5.7
0